2003
DOI: 10.1203/01.pdr.0000072781.93856.e6
|View full text |Cite
|
Sign up to set email alerts
|

Knee Articular Cartilage Development in Children: A Longitudinal Study of the Effect of Sex, Growth, Body Composition, and Physical Activity

Abstract: The aim of this study was to describe the effect of sex, growth, Tanner stage, and physical activity on knee articular cartilage volume development. A total of 74 randomly selected male and female children aged 9 -18 y were measured on two occasions at an average interval of 1.6 y (range 1.3-1.9). Articular cartilage volume was determined at the patella, medial tibial, and lateral tibial compartments by processing images acquired in the sagittal plane using T1-weighted fat saturation magnetic resonance. Height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 22 publications
7
102
2
2
Order By: Relevance
“…The prevalence of radiographic OA was similarly lower in exercisers (20% vs 32%), as were total knee scores. Other studies have also reported similar findings 1,3,10,11 , suggesting a protective association of exercise for radiographic OA as well as disability. Importantly, we found very strong and statistically significant evidence for positive effects of exercise on disability ( Figure 1).…”
supporting
confidence: 61%
“…The prevalence of radiographic OA was similarly lower in exercisers (20% vs 32%), as were total knee scores. Other studies have also reported similar findings 1,3,10,11 , suggesting a protective association of exercise for radiographic OA as well as disability. Importantly, we found very strong and statistically significant evidence for positive effects of exercise on disability ( Figure 1).…”
supporting
confidence: 61%
“…While previous studies have reported that increasing BMI is positively associated with knee joint space narrowing in subjects with knee OA (2,26), there is no significant association between BMI and joint space area or width in normal knees (27). BMI was not associated with incident knee joint space narrowing (28) and the loss of knee cartilage volume in OA knees (19), and knee cartilage volume in overweight children did not differ significantly from that in normal children, either cross-sectionally or longitudinally (29). However, BMI has been inversely associated with tibial cartilage volume standardized for bone size (reflecting cartilage thickness) in men (21).…”
Section: Discussionmentioning
confidence: 80%
“…Triathletes have thicker cartilage in their patellae, but thinner cartilage in their medial femoral condyles, than do agematched inactive study volunteers (6). In children, vigorous self-reported activity in the previous 2 weeks was associated with an accretion of cartilage compared with children with no reports of vigorous activity (7).…”
Section: Introductionmentioning
confidence: 92%